2004
DOI: 10.1007/s00439-004-1123-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA polymorphisms as risk factors for Parkinson?s disease and Parkinson?s disease dementia

Abstract: The activity of complex I of the mitochondrial respiratory chain has been found to be decreased in patients with Parkinson's disease (PD), but no mutations have been identified in genes encoding complex I subunits. Recent studies have suggested that polymorphisms in mitochondrial DNA (mtDNA)-encoded complex I genes (MTND) modify susceptibility to PD. We hypothesize that the risk of PD is conveyed by the total number of nonsynonymous substitutions in the MTND genes in various mtDNA lineages rather than by singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(24 citation statements)
references
References 43 publications
1
21
2
Order By: Relevance
“…Parkinson’s disease risk is associated with mtDNA haplotype, similar to AD (116118). Changes to mtDNA are also observed in PD, such as mutations and deletions (119121).…”
Section: Mitochondrial Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Parkinson’s disease risk is associated with mtDNA haplotype, similar to AD (116118). Changes to mtDNA are also observed in PD, such as mutations and deletions (119121).…”
Section: Mitochondrial Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Studies have demonstrated that mitochondrial DNA was altered in some PD cases and that this alteration raised the risk of the disease by increasing ROS formation [49]. Deficiencies of mitochondrial complex I have been noted in brain and other tissues in postmortem PD studies [50].…”
Section: Oxidative Stress/mitochondrial Dysfunctionmentioning
confidence: 99%
“…Defects in complex I activity are consistently observed in the substantia nigra of patients with PD (111) suggesting that mitochondrial dysfunction is central to PD pathogenesis. Over half of the proteins encoded by mitochondrial DNA assemble into complex I and certain mitochondrial DNA polymorphisms and haplotypes appear to reduce the risk for developing PD (5; 105), including a specific SNP that results in a threonine to alanine change in NADH3 of complex 1 which strongly associates with this protective effect (127). …”
Section: Mitochondrial Complex I Inhibition and Pdmentioning
confidence: 99%